2012
DOI: 10.1080/00207179.2012.696145
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for recursive/semi-recursive bias-compensating least squares system identification within the errors-in-variables framework

Abstract: Algorithms for the recursive/semi-recursive estimation of the system parameters as well as the measurement noise variances for linear single-input single-output errors-in-variables systems are considered. Approaches based on three offline techniques are presented: namely, the bias eliminating least squares, the Frisch scheme and the extended bias compensating the least squares method. Whilst the underlying equations used within these approaches are identical under certain design choices, the performances of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Thus, a recursive Frisch scheme identification approach is extended to enhance its on-line applicability. It is shown that by incorporating adaptation via the introduction of exponential forgetting, the algorithm is able to compensate for the systematic errors, which arise in the original scheme [10]. Therefore, this adaptive recursive Frisch scheme is able to deal with linear time-varying systems, and it is used in connection with the design of an adaptive control scheme, shown in Section IV-A.…”
Section: Recursive Identification For Adaptive Controlmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, a recursive Frisch scheme identification approach is extended to enhance its on-line applicability. It is shown that by incorporating adaptation via the introduction of exponential forgetting, the algorithm is able to compensate for the systematic errors, which arise in the original scheme [10]. Therefore, this adaptive recursive Frisch scheme is able to deal with linear time-varying systems, and it is used in connection with the design of an adaptive control scheme, shown in Section IV-A.…”
Section: Recursive Identification For Adaptive Controlmentioning
confidence: 99%
“…A modification of the Frisch scheme algorithm is proposed here to identify dynamical Errors-In-Variables (EIV) models [10,17]. For the update of the estimated model parameters, a recursive bias-compensating strategy is also www.ijacsa.thesai.org implemented.…”
Section: Recursive Identification For Adaptive Controlmentioning
confidence: 99%
See 3 more Smart Citations